Grounding clinical and cognitive scientists in an interdisciplinary discussion - Ottoboni, Giovanni (Frontiers in Psychology, 2013)
In most clinical approaches the body receives little attention. In cognitive science, in contrast, the embodied and grounded perspective, which emphasises the importance of the body, has been intensively explored over the last decade. The present article aims to engage theorists of embodied cognition and clinical experts in a discussion encouraging them to consider the insights that may arise from each other’s approaches. In a review of the cognitive and clinical literature substantial overlap is revealed between cognitive and clinical domains.